On Some New Milne-type Inequalities for Strongly Convex Functions (Contemporary Mathematics, 2025)
In this paper, we explore new Milne-type fractional integral inequalities, focusing on functions that are strongly convex and differentiable. We use tools like the Hölder inequality and the power-mean inequality to derive these results. Our findings offer a notable improvement over earlier work in this area, providing more advanced and refined mathematical insights.
Keywords: milne-type inequalities, strongly convex function, riemann-liouville fractional integrals, Hölder’s inequality